IN SILICO SCREENING OF POTENT PPARGAMMA AGONISTS AMONG NATURAL ANTICANCER COMPOUNDS OF INDIAN ORIGIN - Gurula, Hemanth; Loganathan, Tholcopiyan; Vashum, Yaongamphi; Pannerselvam, Sudha; Vetrivel, Umashankar; Samuel, Shila (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Naturally occurring anticancer compounds of Indian origin are well-known for potential therapeutic values. A better understanding of the intermolecular interactions of these compounds with peroxisome proliferator-activated receptor gamma (PPARÎ³) is essential, as its activity is reported in many of the cancers involving colon, breast, gastric, and lung. By this study, it is attempted to perform an in silico screening of natural anticancer compounds of Indian origin with PPARÎ³ ligand binding domain (LBD). The potential anticancer leads ranked in this study will also exert an additional advantage of PPARÎ³ activity modulation. As PPARÎ³ is also an important nuclear hormone receptor that modulates transcriptional regulation of lipid and glucose homeostasis and also a key target for many of the anti-diabetic medications, the compounds ranked by this study will also be utilized for other related therapeutic effects. Methods: This study features in silico screening of compounds from Indian Plant Anticancer compounds database against PPARÎ³ LBD main performed Schrodinger glide virtual screening and docking module to delineate potential PPARÎ³ agonists. Finally, the most potential lead was also subjected to molecular dynamics simulation to infer the stability of complex formation. Results: The results reveal that majority of the top ranking compounds that interact with LBD was found to be flavonoids, and all these compounds were found to interact with key residues involved in PPARÎ³ agonist interactions. Conclusion: The leads from this study would be helpful in better understanding of the potential of naturally occurring anticancer compounds of Indian origin toward targeting PPARÎ³. Keywords: Peroxisome proliferator-activated receptor-gamma, Agonists, Docking, Natural compounds, Anticancer. Â